Apoptotic activities of thymoquinone, an active ingredient of black seed (nigella sativa), in cervical cancer cell lines - Arief Ichwan, Solachuddin Jauhari; Al-Ani, Imad Matloub Dally; Bilal, Hakim Gharib; Suriyah, Wastuti Hidayati; Bakhtiar, M. Taher; Ikeda, Masa-Aki; Bilal, Hakim Gharib (The Chinese Physiological Society and Airiti Press Inc, 2014)
Thymoquinone (TQ) is the main constituent of black seed (Nigella sativa, spp) essential oil which shows promising in vitro and in vivo anti-neoplastic activities in different tumor cell lines. However, to date there are only a few reports regarding the apoptotic effects of TQ on cervical cancer cells. Here, we report that TQ stimulated distinct apoptotic pathways in two human cervical cell lines, Siha and C33A. TQ markedly induced apoptosis as demonstrated by cell cycle analysis in both cell lines. More- over, quantitative PCR revealed that TQ induced apoptosis in Siha cells through p53-dependent pathway as shown by elevated level of p53-mediated apoptosis target genes, whereas apoptosis in C33A cells was mainly associated with the activation of caspase-3. These results support previous findings on TQ as a potential therapeutic agent for human cervical cancer.